Costs of Keratinocyte Carcinoma (Nonmelanoma Skin Cancer) and Actinic Keratosis Treatment in the Veterans Health Administration. Issue 9 (September 2016) - Yoon, Jean; Phibbs, Ciaran S.; Chow, Adam; Pomerantz, Hyemin; Weinstock, Martin A.
Abstract : BACKGROUND: The Veterans Health Administration (VHA) provides health care to large numbers of veterans afflicted with keratinocyte carcinoma (KC). OBJECTIVE: To estimate the number of veterans treated for KCs and the related diagnosis, actinic keratosis (AK) and the costs of treating these conditions over a 1-year period. MATERIALS AND METHODS: The authors conducted a cross-sectional analysis of veterans diagnosed with KC or AK during fiscal year 2012 using administrative data on outpatient encounters and prescription drugs provided or paid by VHA. Marginal costs of each condition were estimated from a regression model. The authors estimated counts of outpatient encounters, procedures, and costs related to KC and AK care. RESULTS: In 2012, there were 49, 229 veterans with basal cell carcinoma, 26, 310 veterans with squamous cell carcinoma, and 8, 050 veterans with unspecified invasive KC. There were also 197, 041 veterans with AK and 6, 388 veterans with KC-related diagnoses. The VHA spent 356 million on KC and AK outpatient treatment for procedures, prescription drugs, and other dermatologic care during FY2012. CONCLUSION: There was high prevalence of KC and AK and considerable spending to treat these conditions in VHA. Treatment costs are not generalizable to care provided by non-VHA providers where a facility fee was not incurred. Abstract : Supplemental Digital Content is Available in the Text.